Yaygın Anksiyete Bozukluğu-7 (YAB-7) testi Türkçe uyarlaması, geçerlik ve güvenirliği - (:unkn) unknown (My University, 2013)
Amaç: Çalışmada Türkçeye uyarlanan YAB-7 testinin , geçerlik, güvenirlik ve psikometrik özelliklerinin belirlenmesi amaçlandı. Yöntem: Çalışmaya YAB tanısı konulan 110 hasta 112 sağlıklı gönüllü katıldı. Başlangıç uygulamasının üç hafta sonrasında örneklemin belirli bir bölümüne YAB-7 testi yeniden uygulandı. Yapısal geçerlilik için ana bileşenler analizi, doğrulayıcı faktör analizi, ayırt edici özelliğin belirlenmesi için ROC analizi yapıldı. Değişik kesme değerlerinde pozitif öngörücü değer, negatif öngörücü değer, pozitif ve negatif olabilirlik oranı hesaplandı. Bulgular: YAB grubunda YAB-7 testi toplam puanları kontrol grubuna göre istatistiksel olarak anlamlı yüksek bulundu. YAB-7 testi tüm maddeleri arasında anlamlı ilişki, iç tutarlık ve aralıklı uygulamada iyi kararlılık gösterdiği görüldü. Yapısal geçerlilik için yapılan faktör analizinde YAB-7 testi faktör yapısının orijinal test ile benzer olduğu ve yapısal geçerliliğinin iyi olduğu saptandı. Doğrulayıcı faktör analizinde tek faktörlü yapıya iyi uyum gözlendi. YAB-7 testi için en kabul edilebilir kesme değeri 8 bulundu. Sonuç: YAB-7 Türkçe formunun klinik örneklemde orijinal forma benzer olarak yüksek geçerliğe, güvenilirliğe ve iyi psikometrik özelliklere sahip olduğu saptandı. YAB-7 Türkçe formunun yararlı bir tarama testi olarak değerlendirildi. (Nöropsikiyatri Arflivi 2013; 50: 53-58)

ABSTRACT Objective: Our objective was to identify the validity, reliability and psychometric features of the Turkish adaptation of the Generalized Anxiety Disorder-7 (GAD-7) scale. Method: Patients who were diagnosed with 110 GAD patients and 112 healthy control subjects were included in this study. Three weeks after the initial administration, a certain group of the sample was administered the GAD-7 scale again. The principal components analysis for structural validity and confirmatory factor analysis were performed. Receiver operating characteristics (ROC) curve analysis was performed to identify the distinguishing feature. Positive predictive value, negative predictive value, positive and negative likelihood ratios were calculated at different cut-off levels. Results: The total scores for the GAD-7 scale-Turkish version in the GAD group were found to be statistically significantly higher than those in the control group. A significant correlation was observed between all items of the GAD-7 scaleTurkish version that was found to have good internal consistency and intermittent administration. In the factor analysis performed for assessing the construct validity, the factor structure of the GAD-7 scale-Turkish version was found tosimilar to the original form and the construct validity was found to be good. Good compliance to single factor structure was observed in the confirmatory factor analysis. The most acceptable cut-off point of the GAD-7 scale-Turkish version was found to be 8. Conclusion: The GAD-7 scale-Turkish version, similar to the original form, was found to have a high validity, reliability and good psychometric features in a clinical sample. The Turkish version of the GAD-7 scale was regarded as a useful screening tool. (Arc hives of Neuropsychiatry 2013; 50: 53-58) - be
Validity and reliability study for the Turkish adaptation of the Generalized Anxiety Disorder-7 (GAD-7)scale
Keywords: Nörolojik Bilimler; Psikiyatri